OH and HO2 radical chemistry during PROPHET 2008 and CABINEX 2009 – Part 1: Measurements and model comparison - S. M. Griffith; R. F. Hansen; S. Dusanter; P. S. Stevens; M. Alaghmand; S. B. Bertman; M. A. Carroll; M. Erickson; M. Galloway; N. Grossberg; J. Hottle; J. Hou; et al. (Atmospheric Chemistry and Physics, 2013)
Hydroxyl (OH) and hydroperoxyl (HO2) radicals are key species driving the oxidation of volatile organic compounds that can lead to the production of ozone and secondary organic aerosols. Previous measurements of these radicals in forest environments with high isoprene, low NOx conditions have shown serious discrepancies with modeled concentrations, bringing into question the current understanding of isoprene oxidation chemistry in these environments. During the summers of 2008 and 2009, OH and peroxy radical concentrations were measured using a laser-induced fluorescence instrument as part of the PROPHET (Program for Research on Oxidants: PHotochemistry, Emissions, and Transport) and CABINEX (Community Atmosphere-Biosphere INteractions EXperiment) campaigns at a forested site in northern Michigan. Supporting measurements of photolysis rates, volatile organic compounds, NOx (NO + NO2 and other inorganic species were used to constrain a zero-dimensional box model based on the Regional Atmospheric Chemistry Mechanism, modified to include the Mainz Isoprene Mechanism (RACM-MIM). The CABINEX model OH predictions were in good agreement with the measured OH concentrations, with an observed-to-modeled ratio near one (0.70 ± 0.31) for isoprene mixing ratios between 1–2 ppb on average. The measured peroxy radical concentrations, reflecting the sum of HO2 and isoprene-based peroxy radicals, were generally lower than predicted by the box model in both years.